2011
DOI: 10.1002/pd.2827
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pregnancies complicated by oligohydramnios or anhydramnios of renal origin

Abstract: The prognosis of early onset renal oligohydramnios is poor. Predictive determinants of survival are: GA at diagnosis, nature of renal anomaly (hydronephrosis vs other), and presence of associated anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
4
24
4
1
Order By: Relevance
“…In total, 45% (37% TOP, 8% palliative care) of the counseled families opted primarily against continuation of the pregnancy or postnatal sustained medical treatment. This rate is comparable to that reported in other studies where only TOP was reported and chosen in 46-58% of the cases [16,17].…”
Section: The Third Way: Palliative Caresupporting
confidence: 78%
See 2 more Smart Citations
“…In total, 45% (37% TOP, 8% palliative care) of the counseled families opted primarily against continuation of the pregnancy or postnatal sustained medical treatment. This rate is comparable to that reported in other studies where only TOP was reported and chosen in 46-58% of the cases [16,17].…”
Section: The Third Way: Palliative Caresupporting
confidence: 78%
“…Under these conditions mortality, mostly due to pulmonary hypoplasia, ranges from 30 to 50% and up to 75% (Table 1) [9,[11][12][13][14][15][16][17][18]. However, the high variation in mortality between studies is dependent on the decision regarding TOP and the co-morbidities of liveborn children, both factors which could be misleading in the interpretation of data (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that of 25 liveborn neonates with different antenatal ultrasound findings, nine children (3 with dysplasia, 4 with polycystic kidneys and 2 with hydronephrosis) were not resuscitated because of the associated malformations, and treatment was withheld in an additional seven patients because of the suspected malformations. This study also included patients with very low birth weight, which might have had an impact on morbidity and mortality [43]. Studies which selectively examine fetuses with LUTO are limited by incomplete clinical data despite the probable inclusion of patients with ROH; for example, in a series of 15 patients with urethral valves, five of the patients died [44].…”
Section: Treatment Options (Ante-and Postnatal)mentioning
confidence: 99%
“…In other studies, survivors of ROH are not actively treated, thus increasing mortality. For example, Grijseels et al [43] conducted a retrospective case series in which they analysed the outcome of 71 pregnancies complicated by ROH. They reported that of 25 liveborn neonates with different antenatal ultrasound findings, nine children (3 with dysplasia, 4 with polycystic kidneys and 2 with hydronephrosis) were not resuscitated because of the associated malformations, and treatment was withheld in an additional seven patients because of the suspected malformations.…”
Section: Treatment Options (Ante-and Postnatal)mentioning
confidence: 99%